Primary cutaneous B‐cell lymphoma other than marginal zone: clinicopathologic analysis of 161 cases: Comparison with current classification and definition of prognostic markers. (26th September 2016) - Lucioni, Marco; Berti, Emilio; Arcaini, Luca; Croci, Giorgio A.; Maffi, Aldo; Klersy, Catherine; Goteri, Gaia; Tomasini, Carlo; Quaglino, Pietro; Riboni, Roberta; Arra, Mariarosa; Dallera, Elena; et al.
Abstract: Categorization of primary cutaneous B‐cell lymphomas (PCBCL) other than marginal zone (MZL) represents a diagnostic challenge with relevant prognostic implications. The 2008 WHO lymphoma classification recognizes only primary cutaneous follicular center cell lymphoma (PCFCCL) and primary cutaneous diffuse large B‐cell lymphoma, leg type (PCDLBCL‐LT), whereas the previous 2005 WHO/EORTC classification also included an intermediate form, namely PCDLBCL, other. We conducted a retrospective, multicentric, consensus‐based revision of the clinicopathologic characteristics of 161 cases of PCBCL other than MZL. Upon the histologic features that are listed in the WHO classification, 96 cases were classified as PCFCCL and 25 as PCDLBCL‐LT; 40 further cases did not fit in the former subgroups in terms of cytology and/or architecture, thus were classified as PCDLBCL, not otherwise specified (PCDLBCL‐NOS). We assigned all the cases a histogenetic profile, based on the immunohistochemical detection of CD10, BCL6, and MUM1, and a "double hit score" upon positivity for BCL2 and MYC. PCDLBCL‐NOS had a clinical presentation more similar to PCFCCL, whereas the histology was more consistent with the picture of a diffuse large B‐cell lymphoma, as predominantly composed of centroblasts but with intermixed a reactive infiltrate of small lymphocytes. Its behavior was intermediate between the other two forms, particularly when considering only cases with a "non‐germinal B‐cell" profile, whereas "germinal center" cases resembled PCFCCL. Our data confirmed the aggressive behavior of PCDLBC‐LT, which often coexpressed MYC and BCL2. The impact of single factors on 5‐year survival was documented, particularly histogenetic profile in PCDLBCL and BCL2 translocation in PCFCCL. Our study confirms that a further group—PCDLBCL‐NOS—exists, which can be recognized through a careful combination of histopathologic criteria coupled with adequate clinical information. Abstract : This article deals with a series of 161 cases of primary cutaneous, nonmarginal zone B‐cell lymphoma (BCL), which we retrospectively reviewed. We were able to identify a subset of cases, which we classified as primary cutaneous diffuse large BCL, not otherwise specified, displaying intermediate features—both histologic and clinical—between primary cutaneous follicular and "leg type" lymphoma. We also highlighted the relevance of immunohistochemical characterization—particularly the definition of the histogenic profile and BCL2/MYC expression—as well as of detection of BCL2 translocation in identifying prognostic subsets.